Evaluation of color matching and microhardness of two different universal-shade resin composites: an in-vitro study - Khaled Mahmoud Hijazi; Ahmed Fawzy Abo Elezz; Amr Faisal Ghonaim (BMC Oral Health)
Abstract Background Dentists have started to use universal shade resin composites to simplify shade selection. This in vitro study assessed the color matching of two distinct universal shade resin composites (OMNICHROMA® and ONEshade™) following immersion in staining solution and their microhardness during thermocycling. Methods For color matching evaluation, forty maxillary sound human premolars were collected. Only A3 shaded teeth were chosen after VITA Easyshade V recorded the color coordinates of the teeth via the CIELab color system before interventions. After that, the teeth were randomly allocated into two groups according to the tested materials, with twenty teeth included in each group (n = 20). The teeth were then prepared with class V cavity preparations, the group (M1) teeth were restored with Omnichroma, and the group (M2) teeth were restored with Oneshade. All teeth were evaluated after 24 h of restoration (T1), after 3 months of immersion in tea solution (T2) and after 6 months of immersion in tea solution (T3). To evaluate color matching, both instrumental and visual color changes were recorded. For microhardness evaluation, forty cylindrical discs were made (20 discs for each composite group M1 and M2). Vickers microhardness measurements were performed via a microhardness testing machine. The samples were measured at baseline (C1), after 2500 thermocycles (C2) and after 5000 thermocycles (C3). Results In accordance with the color matching results, both tested composite materials showed significant color mismatching after immersion in tea solution. In accordance with the surface microhardness evaluation, both tested resin composite materials showed a significant decrease in the Vickers microhardness after thermocycling. Conclusions Following immersion in the staining solution, both evaluated resin composite materials displayed unsatisfactory color matching values in class V restorations. Accelerated aging by thermocycling had an obvious negative effect on the microhardness of the universal shade resin materials.